O desenvolvimento de competências de professores pré-serviço de Letras - Língua Inglesa no contexto do Programa Idiomas sem Fronteiras - Brick, Tatiana Vasconcelos (2019)
One of the main challenges in pre-service English Language Teacher training is to open space in course curricula to include professional practice content, bridging theory and praxis, which is the main goal of the Languages without Borders Program’s training that takes place in the Language Centers of the universities that participate in the Program. The present study aimed to investigate about pre-service English Language Teachers views regarding the development of the five competences in their training under the LwB Program, according Almeida Filho's (1993,1997, 2004, 2006, 2007 and 2009) theoretical model. The methodology adopted was the case study, in an interpretative research, adopting both qualitative and quantitative methods. After studying the theoretical framework about competences, a questionnaire with the following three sections was prepared: (i) the first section based on studies by Bergsmann et al (2015) and Peacock's model (2009), expanded and reframed according to the reality of the LwB Program, aiming to find out about the participants’ levels of agreement on aspects that should ideally be present in their training; (ii) the second one is about the degree of impact that the completion of assignments has in the participants’ professional development; and (iii) the third one is about positive and negative aspects of this training, based on open answer questions. The questionnaire was applied to all scholarship pre-service English Language Teacher who were linked to the LwB Program until April 2019, with 284 participants in total, that is, 95% of these teachers. In light of the results, most agree that the training in the Language Centers collaborates to develop especially their professional, applied and implied competences, and that autonomy and critical-reflexive thinking are encouraged. Almost all agree that they will be prepared to act in classroom at the end of the training, and that the assignments carried out during this process have a great impact on their professional development and their teaching practice’s competences. In short, according to these teachers' point of view, the formative process in the context of the LwB Program has contributed to the development of the five competences, improving their pedagogical practice and providing quality English teaching-learning process in the country. Keywords: Languages without Borders Program; Languages – English pre-service teachers’ training; Competences development; Teaching practice.